HPV Testing for Cervical Cancer in Romania: High-Risk HPV Prevalence among Ethnic Subpopulations and Regions - Minodora Bianca Ilisiu (Ubiquity Press, 2019)
Background: Romania has had one of the highest rates of cervical cancer incidence and mortality in Europe for decades. Data on the high-risk human papillomavirus (hrHPV) prevalence within the Romanian population are crucial for cervical cancer intervention in high risk groups. The aim of this study was to determine the prevalence of hrHPV infection in Romania, identifying high-risk areas for cervical cancer prevention efforts. Methods: The target population of this study were women of all forms in Romania, including ethnic minorities, women from urban and rural areas, and women in various regions. Women with no history of precancerous or cancerous lesions were offered hrHPV screening. The specimens were tested with Hybrid Capture 2 (HC2) DNA test. Age-standardized hrHPV prevalence rates with 95% confidence intervals (CI) were estimated. Results: hrHPV results of 2060 women aged 18 to 70 years were analyzed. The highest hrHPV prevalence rates were observed among: Romanians (17.9%; 95 CI: 15.5–20.7%), Hungarians (16.6%; 95% CI: 13.1–20.8%), Russians (15.6%; 95% CI: 11.3–21.3%), women living in North (19.2%; 95% CI: 16.5–22.3%), and West regions (23.0%; 95 CI: 18.6–28.0%), and women living in urban areas (20.0%; 95 CI: 18.5–28.0%). hrHPV prevalence rates were lower for the Roma population (7.8%; 95% CI: 4.7–12.5%). Conclusions: These hrHPV prevalence rates in a high cervical cancer incidence country provide baseline information for targeted cervical cancer intervention strategies as well as a baseline to measure the impact of hrHPV vaccination in the future.